Wizerunek dobrego człowieka w sanskryckiej antologii Subhāṣitaratnakoṣa - Pigoniowa, Mariola (Gajt Wydawnictwo 1991 s.c., 2018)
In a section of the Sanskrit anthology Subhāṣitaratnakoṣa there are 40 poems by various authours the main subject of which is the description of the good man. In the present paper an analysis of some of these poems is given (e. g. 1238, 1239, 1229, 1213, 1215, 1249, 1225, 1243, 1235,1230). It is pointed out that the majority of qualities which mark good man are also those of the brāhmaṇa and kṣatriya, categories of people defined in the Mahābhārata, Bhagavadgītā, and also in one of the Dharmasūtras (Vasiṣṭhadharmasūtra).
Keywords: Subhāṣitaratnakoṣa; Mahābhārata; Bhagavadgītā; Vasiṣṭhadharmasūtra